2023
DOI: 10.30935/ojcmt/13117
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of social media exposure patterns on people’s belief in fake news during COVID-19: A cross-gender study

Abstract: During COVID-19, fake news on social media seriously threatened public health. As a solution to this problem, this study examined how social media exposure patterns affect people being deeply harmed by fake news. Based on cognitive dissonance theory, this study investigated the effect of intentional and incidental exposure on belief in fake news through the mediating role of confirmation bias. The results show that intentional exposure positively influences confirmation bias and belief in fake news. Incidental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Depending on the groups that are relevant to an individual, specific sources of information are trusted and therefore sought out, while others are rejected, or discussion partners are avoided or preferred. Furthermore, it can be observed that when information is sought in a targeted manner (intentional exposure), e.g., using a trusted channel, people are more likely to believe it than when they come across it by accident (incidental exposure) (51).…”
Section: Social Normsmentioning
confidence: 99%
“…Depending on the groups that are relevant to an individual, specific sources of information are trusted and therefore sought out, while others are rejected, or discussion partners are avoided or preferred. Furthermore, it can be observed that when information is sought in a targeted manner (intentional exposure), e.g., using a trusted channel, people are more likely to believe it than when they come across it by accident (incidental exposure) (51).…”
Section: Social Normsmentioning
confidence: 99%
“…Social media are also known as a platform, where misinformation flourishes and cannot easily be refuted (Sharma et al, 2017;Vraga & Bode, 2017;Wu & Mustafa, 2023). Information on social media suffers from a lack of professional gatekeepers to monitor the content, as the public themselves have become producers of information (Chon & Kim, 2022).…”
Section: Research Articlementioning
confidence: 99%